The Relevance of Consumer Behavior and Competition of Products to Levying Excise Duties on Cosmetics under EU Law - Mickutė, Karolina (Teisė, 2019)
In Bene Factum, the Court of Justice of the European Union ruled that cosmetic products should be exempt from excise duty on alcoholic beverages if they contain ethyl alcohol regardless the actual use of the product (consumer behavior). In order to assess the prerequisites for the proper application of EU law in the field of excise duty, the article assesses the mechanism of determining product competition at the EU and International Trade Law levels, which is important for the classification of products for tax purposes, including the extent to which cosmetic products compete with alcoholic beverages, how private business is limited by consumer habits, and possible governmental intervention in this context.
Keywords: EU law; Excise duty; Exemptions; Definition of “products not for human consumption”; consumer behavior; cosmetics